2018
DOI: 10.1016/j.watres.2018.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Differential development of Legionella sub-populations during short- and long-term starvation

Abstract: Legionellae are among the most important waterborne pathogens in industrialized countries. Monitoring and surveillance of Legionella in engineered water systems is usually performed with culture-based methods. Since the advent of culture-independent techniques, it has become clear that Legionella concentrations are often several orders of magnitude higher than those measured by culture-based techniques and that a variable proportion of these non-culturable cells are viable. In engineered water systems, the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 29 publications
0
36
0
Order By: Relevance
“…All microcosms used in ELISA and FCM were prepared in a standardized procedure described in detail elsewhere [ 18 ]. In brief, Legionella strains were grown in liquid buffered yeast extract (liBYE, modified [ 24 ]) and sub-cultured once, until the population reached the stationary phase, assessed by optical density (OD) measurement (OD-values of stationary phase: 3–4 depending on the strain, OD analysis was conducted after eight-fold dilution in liBYE).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…All microcosms used in ELISA and FCM were prepared in a standardized procedure described in detail elsewhere [ 18 ]. In brief, Legionella strains were grown in liquid buffered yeast extract (liBYE, modified [ 24 ]) and sub-cultured once, until the population reached the stationary phase, assessed by optical density (OD) measurement (OD-values of stationary phase: 3–4 depending on the strain, OD analysis was conducted after eight-fold dilution in liBYE).…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 10 8 cells mL − 1 (final concentration, using a conversion factor comparing OD values with total cell counts determined by SYBR green 1/propidium iodide staining [ 26 ] and epifluorescence microscopy (EFM) [ 27 ]) were inoculated to sterile glass bottles prefilled with 350 mL of autoclaved ultrapure water (starvation microcosms). After an initial sampling, all microcosm bottles were incubated at 45 °C without shaking and periodically sampled by pouring out 15 mL of each bottle and aliquoting the sample for further analysis [ 18 , 21 ]. 500 μl were used for immunofluorescence (IF)-FCM.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The trend of lag-1 gene loss or deactivation was not observed among longitudinal ST1 healthcare facility-associated isolates from a cluster sequenced in a recent study by David and colleagues (David et al, 2017). However, a study on starvation of L. pneumophila in ultrapure water showed that in a short-term period, the viable cell numbers of all mAb 3/1-positive strains decreased strongly compared to the other strains suggesting a negative selection for lag-1 function in some water environments (Schrammel et al, 2018). Overall, these data indicate that the presence of a functional lag-1 correlates with enhanced resistance to serum killing.…”
Section: Lag-1 Confers Resistance To Killing By Human Plasma and Bronmentioning
confidence: 86%